2007
DOI: 10.1007/s11096-006-9072-0
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of a pharmaceutical care service: prescriptionists’, pharmacists’ and doctors’ views

Abstract: When prescriptionists and pharmacists apply the pharmaceutical care concept and work with PMRs, the patients are more likely to meet confident professionals that are more aware of the individual behind the drug therapy. This will hopefully contribute to informed, motivated medicine users that feel secure in their interactions with their pharmacy and receive, not only drugs, but treatment support. For such a service to be effective, however, it is vital to ensure that the doctors are fully co-operative.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
22
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 24 publications
3
22
0
Order By: Relevance
“…The change was significant (p , 0.001). At the start of the internship, 25% of the students were categorized as reflective (level [4][5][6] and at the end 60 % were categorized as reflective (p , 0.114). Viewed proportionally, 58% increased their levels of reflection between the start and the end of the internship, 31% maintained the same level of reflection, and 11% decreased their level.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The change was significant (p , 0.001). At the start of the internship, 25% of the students were categorized as reflective (level [4][5][6] and at the end 60 % were categorized as reflective (p , 0.114). Viewed proportionally, 58% increased their levels of reflection between the start and the end of the internship, 31% maintained the same level of reflection, and 11% decreased their level.…”
Section: Resultsmentioning
confidence: 99%
“…2 This role puts great demands on pharmacists as practitioners, and requires continuous reevaluation of their professional knowledge and behavior and an adaptation to each patient that they meet. 3,4 Pharmacists' confidence in their professional role is crucial because they cannot allow their decision making to be halted when faced with challenging or new situations and problems. 1 This confidence can be reached by continuously reflecting upon experiences, and by developing a greater understanding of the profession and its contribution to the healthcare system as a whole.…”
Section: Introductionmentioning
confidence: 99%
“…(3) Believes she/he is capable of performing PhC successfully, because she/he has the necessary skills and does not anticipate important barriers. Potential barriers include inadequate knowledge of PhC, underdeveloped communication skills and insufficient physical space and time in the pharmacy [25,26]. their professional behaviour completes the theoretical framework of the models.…”
Section: The Transtheoretical Modelmentioning
confidence: 99%
“…[9,10] Recent studies concluded that the known clinical pharmacy achievements are highly determined by lots of factors such as knowledge, attitude and perception of HCPs toward clinical pharmacy profession. [11,12] Thus, it"s essential and critical to ensure and maintain HCPs positive attitude and perception toward clinical pharmacists (CPs) direct contribution to patient care provision. [3] The current study aimed to investigate the level of acceptance of integrating CPs into the healthcare team.…”
Section: Introductionmentioning
confidence: 99%